Quid et unde malum: attualità di Agostino - Alici, Luigi (E-theca OnLineOpenAccess Edizioni, 2025)
By taking into account Augustine’s attitude towards Manichaeism and Neoplatonism, this paper offers an ethical-anthropological analysis of the topic of evil in his works. It is argued that Augustine’s differentiation between ontological good and moral evil has relevant implications for contemporary debates on the topic, in particular, for those inspired by Hans Jonas.